Vestibular migraine: clinical and epidemiological aspects - Morganti,Ligia Oliveira Gonçalves (2016)
ABSTRACT INTRODUCTION: Vestibular migraine (VM) is one of the most often common diagnoses in neurotology, but only recently has been recognized as a disease. OBJECTIVE: To analyze the clinical and epidemiological profile of patients with VM. METHODS: This was a retrospective, observational, and descriptive study, with analysis of patients' records from an outpatient VM clinic. RESULTS: 94.1% of patients were females and 5.9% were males. The mean age was 46.1 years; 65.6% of patients had had headache for a longer period than dizziness. A correlation was detected between VM symptoms and the menstrual period. 61.53% of patients had auditory symptoms, with tinnitus the most common, although tonal audiometry was normal in 68.51%. Vectoelectronystagmography was normal in 67.34%, 10.20% had hyporeflexia, and 22.44% had vestibular hyperreflexia. Electrophysiological assessment showed no abnormalities in most patients. Fasting plasma glucose and glycemic curve were normal in most patients, while the insulin curve was abnormal in 75%. 82% of individuals with MV showed abnormalities on the metabolism of carbohydrates. CONCLUSION: VM affects predominantly middle-aged women, with migraine headache representing the first symptom, several years before vertigo. Physical, auditory, and vestibular evaluations are usually normal. The most frequent vestibular abnormality was hyperreflexia. Most individuals showed abnormality related to carbohydrate metabolism.